Driving on the brain: An investigation of cerebrovascular accident and driving, and the development of a post-stroke driver profile - Blane, Alison Louise (Curtin University, 2017)
Assessing post-stroke driving safety is a multifactorial issue. Therefore, this thesis developed a post-stroke driver profile, investigating the appropriateness of assessments; including on-road observations, simulated driving and cognitive assessments in licensed post-stroke drivers. It also assessed the influence of post-stroke cognition on driving performance, task demand, and investigated the compensation strategies used by post-stroke licensees. The results are useful for practitioners and policy makers, and in driving assessments, rehabilitation programmes and for future research.